Analyseinstrumente zum mathematischen Modellieren mit digitalen Medien und Werkzeugen (mathematica didactica, 2022)
Combining reality-based problems with digital media and tools brings new difficulties and challenges for students. Using two different modelling cycles, we analyze student modelling routes, who could solve the modelling problem with the help of technology. Models describing such processes are discussed and advantages as well as disadvantages of the two analysis tools are identified. Qualitative analyses are described in detail and their results are connected to underlaying theoretical approaches.